Gaya Kepemimpinan Tokoh Informal dan Tingkat Partisipasi Masyarakat dalam Program Desa Mandiri Pangan - Fitriadi, Mochammad Yunus Gerry; Sumardjo, Sumardjo; Hamzah, Hamzah (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
Some studies show that community participation in the Demapan program is relatively low. This study aims to analyze the relationship between informal leader?s leadership style with the level of community participation in the Demapan program and to analyze what factors are related to the level of community participation in the Demapan program. This research method is surveyed by cluster random sampling technique. This research relies on the analysis of theory about the informal leader?s leadership style that effectively increases the community participation in Demapan program is democratic. Factors that related positivity to community participation are the age of program participants, government support and suitability of facilities and infrastructure especially business equipment and capital support. To increase the effectiveness of community participation in the Demapan program is to change the style of leadership of informal leaders who tend laissez-faire into a style of democratic leadership.Keywords: Rural, Leadership Style, Participation Level of Community, Informal Leader ABSTRAKBeberapa penelitian menunjukkan partisipasi masyarakat dalam program Demapan relatif rendah. Penelitian ini bertujuan untuk menganalisis hubungan gaya kepemimpinan tokoh informal dengan tingkat partisipasi masyarakat dalam program Demapan dan menganalisis faktor apa saja yang berhubungan dengan tingkat partisipasi masyarakat dalam program Demapan. Metode penelitian ini adalah survey dengan teknik cluster random sampling. Penelitian ini bertumpu pada analisis teori tentang gaya kepemimpinan tokoh informal yang efektif meningkatkan partisipasi masyarakat dalam program Demapan adalah demokratis. Faktor yang berhubungan positif dengan partisipasi masyarakat adalah usia peserta program, dukungan pemerintah dan kesesuaian sarana dan prasarana terutama peralatan usaha dan dukungan modal. Untuk meningkatkan keefektifan partisipasi masyarakat dalam program Demapan yaitu merubah gaya kepemimpinan tokoh informal yang cenderung laissez faire menjadi gaya kepemimpinan demokratis.Kata kunci: Desa, Gaya Kepemimpinan, Partisipasi Masyarakat, Tokoh Informal